Tuberculosis, HIV, food insecurity, and poverty in rural Zambia : an ethnographic account of the Southern province - Chileshe, Mutale (University of Cape Town, 2014)
Includes bibliographical references (leaves 162-184). === The thesis is based on fieldwork conducted in Pemba/Batoka in the Southern part of Zambia between September 2006 and July 2007. The core approach of fieldwork was case studies of nine people (four women and five men) who were suffering from TB, and their households; and a comparative sample of seven households that did not have a TB patient. The participatory methods included time lines, seasonal calendars, observation and semi-structured interviews. The main aim of all methods was to find out how the nine TB patients experienced life in a wider social context, the problems they faced within their households in terms of food security and accessing both TB and HIV treatment.